P24 antigen detection, viral isolation, DNA-PCR and in vitro antibody production for the diagnosis of HIV-1 latent infection in heterosexual women at high risk for HIV-1 infection. Issue 2 (April 1995) - Di Stefano, M; Fiore, J R; Chironna, M; Buccoliero, G; Romanelli, C; La Grasta, L; Quarto, M; Angarano, G; Pastore, G
Abstract : INTRODUCTION--The report of the existence of at-risk seronegative subjects, latently infected with HIV-1 and producing "in vitro" HIV-1 specific antibodies, prompted the authors to evaluate extensively twenty-five heterosexual HIV-1 seronegative women at high risk for HIV-1 infection. MATERIAL AND METHODS--The capability of peripheral blood mononuclear cells from such subjects to produce "in vitro" HIV-1 specific antibodies after pokeweed-mitogen stimulation, was studied. Silent HIV-1 infection was investigated by HIV-1 DNA PCR, viral isolation and serum p24 Ag detection at entry and after 6 and 12 months. RESULTS--Three seroconversions took place within 12 months, but no HIV-1 infections were found in the absence of detectable serum anti HIV-1 antibodies, even in subjects who apparently produced such antibodies in vitro. The antibodies produced in vitro by the seronegative women studied appeared of narrow specificity, reacting mainly with gp 160/120 envelope glycoproteins. CONCLUSIONS--A strong concordance was found between the serological status and the other markers for HIV-1 infection, suggesting that the phenomenon of HIV-1 "latent infection" is a very rare event, if it occurs at all. Seronegative women sexually exposed to the virus may produce in vitro anti HIV-1 antibodies of narrow specificity in the absence of other signs of infection and this phenomenon might be related to an anamnestic response to the virus.